Preservice primary teachers' three dimensional thinking skills - (:unkn) unknown (ELSEVIER SCIENCE BV, 2009)
This study investigates primary school preservice teachers' abilities in relation to figures, one of the basic concepts of geometry, and more specifically, to name figures; to draw solid figures from their given corresponding nets and the nets from the solids; and to sketch a three-dimensional structure on the plane from a given perspective. The sample consisted of 62 year 1 and 119 year 3 students registered in the Primary School Education programme at Selcuk University, Education Faculty, Department of Elementary Education in the 2007-2008 academic year. The study had a survey research design and a test consisting of open-ended items was administered for data collection. Descriptive statistics and t-tests were used in data analysis. The results indicated that preservice teachers encountered difficulties in naming rectangular prism-square prism and rectangular pyramid-rectangular prism as well as in drawing these three-dimensional solid figures from their corresponding nets. Moreover, first year students achieved a higher average success rate than third year students. In their undergraduate studies, preservice teachers were not provided with opportunities to take part in the process via a curriculum which involves activities, materials and projects that develop spatial skills. (C) 2009 Elsevier Ltd. All rights reserved
Keywords: Geometry; figure; three-dimensional structure; prism; pyramid; spatial ability